A Newly Proposed Fixed-Time Terminal Sliding Mode Controller for a Class of Nonlinear Systems: Throttle Valve Study - Mostafa Rabbani; Reihaneh Kardehi Moghaddam; Ehsan Razavi; Naser Pariz (Modelling and Simulation in Engineering)
Throttle valves are widely used in piping processes including oil and gas energy. Quick and accurate control of the position of the valve and reducing the dependency on the initial conditions of the valve not only leads to a decrease in energy consumption but also takes advantage of increasing the productivity of the generator and saving the fuel entered into the turbine. In this article, a newly proposed fuzzy-regulated fixed-time terminal sliding mode control (TSMC) is performed for the nonlinear second-order electronic throttle valve (ETV) system in the presence of uncertainty and external disturbances. In addition, a fuzzy rule base is applied to regulate the coefficients of the switching control law to improve the convergence of state variables to the sliding surface and reduce the chattering phenomenon. The proposed method is compared with the fixed-time TSMC and backstepping sliding mode control methods, and the results show that the designed controller works well in reducing the chattering phenomenon by 38.66% and reducing overshoot by 75.46%. Also, increasing the convergence speed of the transient response to 0.33 s, reducing the tracking error, improving system robustness, and getting free from initial conditions are some advantages of the proposed method.